Disinfecting Slush Machines by an Innovative Near Ultraviolet Light Emitting Diode (UV LED) Technological System - Salini, C.; Amodeo, D.; Cevenini, G.; Nante, N.; De Palma, I.; Messina, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Microbial contamination of food and beverages is a topic of great interest. The most innovative technologies take advantage from UV light. This study aimed to evaluate a possible configuration of a nUV LED device at a wavelength of 405 nm installed on slush machines in order to reduce the microbial contamination. Study Design and Methods. The study was conducted in the Department of Molecular and Developmental Medicine, University of Siena, Italy. A nUV LED device with 408 nm wavelength was installed and used on the slush machines. The inner walls of the machine tanks were fouled with contaminated slush, to evaluate the effectiveness of nUV radiation in reducing microbial contamination over time. Results. Experiment results on the slush machine showed a statistically significant logarithmic microbial reduction, in relation with the distance from the nUV LED light source. It has also been shown that the reduction of microbes is possible with a proper management of some parameters: the exposure time, the power and wavelength of the light source, the distance and the obstacles between the light source and the target to be irradiated. Conclusion. To reduce the incidence of foodborne diseases it is necessary to take all necessary precautionary measures, and the use of nUV technology has proved to be a crucial element in achieving this goal.